Fuel cell membrane electrode, preparation method thereof and fuel cell
By introducing hydrophilic and hydrophobic nanoparticles into the cathode catalytic layer of the fuel cell, the problem of oxygen transmission difficulties caused by high water content of the fuel cell cathode is solved, and the output power density is significantly improved.
Patent Information
- Application Number
- CN202311352554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
The fuel cell cathode has difficulty in transmitting oxygen due to high water content, which affects the output power.
A hydrophilic nanoparticles are added to the first catalytic layer adjacent to the proton exchange membrane, and a hydrophobic nanoparticles are added to the outermost layer of the cathode catalytic layer to construct a gradient design from hydrophilic to hydrophobic.
The problem of proton conduction near the proton exchange membrane side is solved, and the capillary force gradient of the pores of the catalytic layer is formed, which is conducive to the transmission of oxygen and the discharge of liquid water, and improves the output power density of the fuel cell.
Smart Images

Figure CN119852456A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of fuel cell membrane electrodes, and in particular to a fuel cell membrane electrode, a preparation method thereof and a fuel cell. Background Art
[0002] The membrane electrode assembly (MEA) is the core unit of the proton exchange membrane fuel cell, and the cathode catalyst layer is the core part of the MEA. The electrochemical reaction only occurs in the cathode catalyst layer (CL). Water and oxygen move through the secondary pores of the CL and then transported to the catalyst surface. The generated water is discharged through these pores to the gas diffusion layer (GDL) and then discharged from the fuel cell. Therefore, the ability to transport oxygen and water greatly limits the power generated by the fuel cell. After the development in recent years, the CL structural design has made a breakthrough, but the power density is still limited. Compared with the anode side, the cathode has a high water content and the oxygen reduction process is complicated, so the structural design of the cathode catalyst layer is particularly important.
[0003] A traditional method is to help the cathode catalyst layer drain water by matching it with a more hydrophobic gas diffusion layer (GDL), but this method cannot effectively solve the problem of water vapor transport inside the catalyst layer, especially the catalyst layer close to the proton exchange membrane side; another commonly used method is to perform a gradient design of the ionomer for the cathode catalyst layer. This method can improve water vapor transport to a certain extent, but seriously affects the utilization rate of the catalyst and also leads to the problem of reduced output power. Summary of the invention
[0004] The main purpose of the present invention is to provide a fuel cell membrane electrode, a preparation method thereof and a fuel cell, so as to solve the problem in the prior art that the high water content in the cathode of the fuel cell leads to difficulty in oxygen transmission and affects the output power.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a fuel cell membrane electrode is provided, comprising a cathode catalyst layer, a proton exchange membrane and an anode catalyst layer, wherein the cathode catalyst layer comprises a first catalyst layer, a second catalyst layer and a third catalyst layer arranged in sequence, wherein the first catalyst layer is adjacent to the proton exchange membrane; the first catalyst layer, the second catalyst layer and the third catalyst layer each independently comprise a catalyst and an ionomer, and the first catalyst layer contains hydrophilic nanoparticles, and the third catalyst layer contains hydrophobic nanoparticles.
[0006] Further, the hydrophilic nanoparticles include any one or more of nano-sized titanium dioxide particles, nano-sized hydrophilic fumed silica particles, nano-sized aluminum oxide particles, nano-sized polyvinyl alcohol particles, and nano-sized microcrystalline cellulose particles;
[0007] Preferably, the specific surface area of the hydrophilic nanoparticles is 100-400 m 2 / g;
[0008] Preferably, the mass ratio of the hydrophilic nanoparticles to the catalyst in the first catalytic layer is 0.05-0.8:1.
[0009] Further, the hydrophobic nanoparticles include any one or more of nano-sized PTFE particles, nano-sized silicone resin particles, nano-sized hydrophobic fumed silica particles, and nano-sized fluoride hydrophobic agent particles;
[0010] Preferably, the specific surface area of the hydrophobic nanoparticles is 100 to 400 m 2 / g;
[0011] Preferably, the mass ratio of the hydrophobic nanoparticles to the catalyst in the third catalytic layer is 0.02-0.40:1.
[0012] Furthermore, the catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer are independently Pt / C or Pt-alloy / C catalysts. Preferably, the content of platinum in the catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer is 20-60wt%.
[0013] Furthermore, the Pt loading of the first catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the second catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the third catalytic layer is 0.05-0.15 mg / cm 2 .
[0014] Further, the ionomer is selected from any one or more of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, polymethylphenylsulfonic acid siloxane resin and sulfonated polystyrene-polyethylene copolymer resin;
[0015] Preferably, in the first catalytic layer and / or the second catalytic layer and / or the third catalytic layer, the mass ratio of the ionomer to the carbon in the catalyst is 0.2 to 2.0:1.
[0016] According to another aspect of the present invention, a method for preparing a fuel cell membrane electrode as any of the above-mentioned ones is provided, and the preparation method comprises: step S1, setting a first catalytic layer dispersion on a surface of a proton exchange membrane to form a first catalytic layer, the first catalytic layer dispersion comprising a catalyst, an ionomer, hydrophilic nanoparticles and a solvent; step S2, setting a second catalytic layer dispersion on the surface of the first catalytic layer to form a second catalytic layer, the second catalytic layer dispersion comprising a catalyst, an ionomer and a solvent; step S3, setting a third catalytic layer dispersion on the surface of the second catalytic layer to form a third catalytic layer, the third catalytic layer dispersion comprising a catalyst, an ionomer, hydrophobic nanoparticles and a solvent.
[0017] Further, the content of the catalyst in the first catalyst layer dispersion is 1-20wt%;
[0018] and / or, the content of the catalyst in the second catalyst layer dispersion is 1-20wt%;
[0019] And / or, the content of the catalyst in the third catalytic layer dispersion is 1-20 wt%.
[0020] Furthermore, the solvents in the first catalytic layer dispersion liquid, the second catalytic layer dispersion liquid and the third catalytic layer dispersion liquid are independently any one or more of water, methanol, ethanol, ethylene glycol, propanol, isopropanol and glycerol.
[0021] According to another aspect of the present application, a fuel cell is provided, which includes any one of the above-mentioned fuel cell membrane electrodes, or a fuel cell membrane electrode prepared by any one of the above-mentioned preparation methods.
[0022] By applying the technical solution of the present invention, hydrophilic nanoparticles are added to the first catalytic layer adjacent to the proton exchange membrane (PEM), and hydrophobic nanoparticles are added to the outermost layer of the cathode catalytic layer, i.e., the third catalytic layer. A gradient design from hydrophilic to hydrophobic is constructed from the inside to the outside, which not only solves the proton conduction problem close to the PEM side, but also forms a capillary force gradient in the pores of the catalytic layer, which is beneficial to the transmission of oxygen and the discharge of liquid water, thereby increasing the output power density of the fuel cell and greatly improving the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 The polarization result curves of Example 1 and Comparative Example 1 according to the present invention are shown. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] As analyzed in the background technology of this application, there is a problem in the prior art that the fuel cell membrane electrode fuel cell cathode has difficulty in oxygen transmission due to high water content, which affects the output power. In order to solve this problem, this application provides a fuel cell membrane electrode, a preparation method thereof and a fuel cell.
[0027] According to a typical embodiment of the present application, a fuel cell membrane electrode is provided, comprising a cathode catalyst layer, a proton exchange membrane and an anode catalyst layer, characterized in that the cathode catalyst layer comprises a first catalyst layer, a second catalyst layer and a third catalyst layer arranged in sequence, wherein the first catalyst layer is adjacent to the proton exchange membrane; the first catalyst layer, the second catalyst layer and the third catalyst layer each independently comprise a catalyst and an ionomer, and the first catalyst layer contains hydrophilic nanoparticles, and the third catalyst layer contains hydrophobic nanoparticles.
[0028] The above-mentioned fuel cell membrane electrode is constructed with a gradient design from hydrophilic to hydrophobic from the inside to the outside by adding hydrophilic nanoparticles in the first catalytic layer adjacent to the proton exchange membrane (PEM) and adding hydrophobic nanoparticles in the outermost layer of the cathode catalytic layer, i.e., the third catalytic layer. This not only solves the problem of proton conduction close to the PEM side, but also forms a capillary force gradient in the pores of the catalytic layer, which is beneficial to the transmission of oxygen and the discharge of liquid water, thereby increasing the output power density of the fuel cell and greatly improving the battery performance.
[0029] In some embodiments of the present application, the hydrophilic nanoparticles include any one or more of nano-sized titanium dioxide particles, nano-sized hydrophilic fumed silica particles, nano-sized aluminum oxide particles, nano-sized polyvinyl alcohol particles, and nano-sized microcrystalline cellulose particles, which have a good effect on improving the water vapor transmission efficiency of the negative electrode catalyst layer, especially when the hydrophilic nanoparticles are nano-sized titanium dioxide particles, the effect is better. Preferably, the specific surface area of the hydrophilic nanoparticles is 100-400m 2 / g, which is beneficial to further improve the water vapor transmission efficiency of the negative electrode catalyst layer.
[0030] In some embodiments of the present application, in order to better balance the water vapor transmission efficiency of the catalytic layer and the catalytic efficiency of the catalyst, the mass ratio of the hydrophilic nanoparticles to the catalyst in the first catalytic layer is 0.05 to 0.8:1, preferably 0.4 to 0.6:1.
[0031] In some embodiments of the present application, the hydrophobic nanoparticles include any one or more of nano-sized PTFE particles, nano-sized silicone resin particles, nano-sized hydrophobic fumed silica particles, and nano-sized fluoride hydrophobic agent particles. The third catalytic layer containing the hydrophobic nanoparticles can better cooperate with the second catalytic layer and the first catalytic layer of the present application, thereby improving the water vapor transmission of the negative electrode catalytic layer and greatly improving the battery performance. In particular, when the hydrophobic nanoparticles are nano-sized PTFE particles, the above effect is better. Preferably, the specific surface area of the hydrophobic nanoparticles is 100 to 400 m 2 / g, which is beneficial to further improve the performance of membrane electrode.
[0032] Among them, hydrophilic fumed silica particles refer to silica powders obtained by hydrolyzing volatile chlorosilanes in a hydrogen-oxygen flame. Hydroxyl groups are retained on the surface of the silica particles, so they are hydrophilic; hydrophobic fumed silica is obtained by chemical reaction between hydrophilic fumed silica and active silanes (such as chlorosilane, hexamethyldisilazane, etc.), and its surface is hydrophobic due to the connection of non-hydrolyzed methyl groups.
[0033] In order to further improve the performance of the membrane electrode and make the hydrophobic nanoparticles play a more significant role, preferably, the mass ratio of the hydrophobic nanoparticles to the catalyst in the third catalytic layer is 0.02 to 0.40:1, preferably 0.2 to 0.4:1.
[0034] In some typical embodiments of the present application, the cathode catalyst layer of the membrane electrode of the fuel cell includes a first catalyst layer, a second catalyst layer and a third catalyst layer arranged in sequence, wherein the first catalyst layer is adjacent to the proton exchange membrane; the first catalyst layer, the second catalyst layer and the third catalyst layer each independently include a catalyst and an ionomer, and the first catalyst layer contains nano-scale titanium dioxide particles, and the third catalyst layer contains nano-scale PTFE particles; preferably, the specific surface area of the nano-scale titanium dioxide particles is 100 to 400 m 2 / g, the mass ratio of nano-sized titanium dioxide particles to catalyst in the first catalytic layer is 0.05-0.8:1; preferably, the specific surface area of the nano-sized PTFE particles is 100-400m 2 / g, and the mass ratio of nano-PTFE particles to catalyst in the first catalytic layer is 0.02-0.40:1.
[0035] The catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer can be selected from the prior art without special requirements. For example, the catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer are independently any one or more of Pt / C and Pt-alloy / C catalysts. In order to further improve the utilization rate of the catalyst and the performance of the membrane electrode, the content of platinum in the catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer is preferably 20-60wt%.
[0036] In some typical embodiments of the present application, the Pt loading of the first catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the second catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the third catalytic layer is 0.05-0.15 mg / cm 2 , so that the catalytic effect of the negative electrode catalyst layer is better, and the comprehensive performance of the membrane electrode and fuel cell is improved.
[0037] The selection of ionomers in the first catalytic layer, the second catalytic layer and the third catalytic layer can also be determined according to the prior art, and there is no special requirement in this application. In some embodiments of this application, the ionomer is selected from any one or more of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, polymethylphenylsulfonic acid siloxane resin and sulfonated polystyrene-polyethylene copolymer resin. The above ionomers have better effects as dispersants, further improving the comprehensive performance of the membrane electrode.
[0038] In some embodiments of the present application, in order to further improve the comprehensive performance of the negative electrode catalyst layer, the mass ratio of the ionomer to the carbon in the catalyst is 0.2 to 2.0:1.
[0039] In some embodiments of the present application, the ionomer is dispersed in a solvent, and its content as a dispersant is 2-40 wt %.
[0040] In some embodiments of the present application, the thickness of the first catalytic layer is 2 to 4 μm; and / or, the thickness of the second catalytic layer is 2 to 4 μm; and / or, the thickness of the third catalytic layer is 2 to 4 μm, so as to better play the role of each catalytic layer, promote the capillary force gradient of the pores of the catalytic layer, be more conducive to the transmission of oxygen and the discharge of liquid water, and significantly improve the output power density of the fuel cell. In some embodiments of the present application, the thickness of the first catalytic layer, the second catalytic layer and the third catalytic layer is the same or close. For example, the difference in thickness of the first catalytic layer, the second catalytic layer and the third catalytic layer is within 1 μm, or within 0.5 μm, or within 0.2 μm, or within 0.1 μm, or within 0.05 μm.
[0041] According to another typical embodiment of the present application, a method for preparing a fuel cell membrane electrode as any of the above-mentioned ones is provided, and the preparation method comprises: step S1, setting a first catalytic layer dispersion on a surface of a proton exchange membrane to form a first catalytic layer, the first catalytic layer dispersion comprising a catalyst, an ionomer, hydrophilic nanoparticles and a solvent; step S2, setting a second catalytic layer dispersion on the surface of the first catalytic layer to form a second catalytic layer, the second catalytic layer dispersion comprising a catalyst, an ionomer and a solvent; step S3, setting a third catalytic layer dispersion on the surface of the second catalytic layer to form a third catalytic layer, the third catalytic layer dispersion comprising a catalyst, an ionomer, hydrophobic nanoparticles and a solvent.
[0042] The fuel cell membrane electrode is constructed from the inside out by adding hydrophilic nanoparticles to the first catalyst layer adjacent to the proton exchange membrane (PEM), and adding hydrophobic nanoparticles to the outermost layer of the cathode catalyst layer, i.e., the third catalyst layer, to form a gradient design from hydrophilic to hydrophobic. This not only solves the proton conduction problem near the PEM side, but also forms a capillary force gradient in the pores of the catalyst layer, which is beneficial to the transmission of oxygen and the discharge of liquid water, thereby increasing the output power density of the fuel cell and greatly improving the battery performance. The above preparation method is simple in process, suitable for process amplification, and can effectively solve the problem of water vapor transmission in fuel cells.
[0043] In some typical embodiments of the present application, the content of catalyst in the first catalytic layer dispersion is 1-20wt%; and / or, the content of catalyst in the second catalytic layer dispersion is 1-20wt%; and / or, the content of catalyst in the third catalytic layer dispersion is 1-20wt%. The dispersion prepared according to the content of the catalyst has a more appropriate concentration, which is convenient for setting up the dispersion of each catalytic layer, and is beneficial to improving the production efficiency of the membrane electrode, and further improving the performance of the cathode catalyst layer of the membrane electrode.
[0044] The solvents in the first catalytic layer dispersion liquid, the second catalytic layer dispersion liquid and the third catalytic layer dispersion liquid can be selected from the prior art, and the present application is not limited thereto. In some embodiments of the present application, the solvents in the first catalytic layer dispersion liquid, the second catalytic layer dispersion liquid and the third catalytic layer dispersion liquid are independently any one or more of water, methanol, ethanol, ethylene glycol, propanol, isopropanol and glycerol. The solvents in the first catalytic layer dispersion liquid, the second catalytic layer dispersion liquid and the third catalytic layer dispersion liquid can be the same or different.
[0045] In some typical embodiments of the present application, the method for preparing the fuel cell membrane electrode further includes: disposing an anode catalyst layer dispersion on another surface of the proton exchange membrane opposite to the first catalyst layer to form an anode catalyst layer.
[0046] The anode catalyst layer dispersion includes a catalyst, an ionomer and a solvent. The catalyst, ionomer and solvent in the anode catalyst layer dispersion can be selected by referring to the prior art, or according to the corresponding components in the first catalyst layer dispersion, the second catalyst layer dispersion and the third catalyst layer dispersion. Preferably, the Pt loading of the formed anode catalyst layer is 0.04-0.15 mg / cm 2 .
[0047] Those skilled in the art can easily prepare the corresponding dispersions by mixing and dispersing the specific components of the first catalytic layer dispersion, the second catalytic layer dispersion, the third catalytic layer dispersion and the anode catalytic layer dispersion. For example, the mixing and dispersing method can be ultrasonic dispersion, ultra-high speed shear dispersion, nano-homogenizer dispersion, mechanical stirring dispersion or ball milling dispersion, etc.
[0048] The first catalyst layer dispersion, the second catalyst layer dispersion, the third catalyst layer dispersion and the anode catalyst layer dispersion can be set in a manner selected from existing technologies, such as slit coating, doctor blade coating, ultrasonic spraying, screen printing and the like.
[0049] According to another typical embodiment of the present application, a fuel cell is provided, which includes any one of the above-mentioned fuel cell membrane electrodes, or a fuel cell membrane electrode prepared by the above-mentioned preparation method.
[0050] Since the fuel cell adopts the above-mentioned fuel cell membrane electrode, it not only solves the proton conduction problem close to the PEM side, but also forms a capillary force gradient in the pores of the catalyst layer, which is beneficial to the transmission of oxygen and the discharge of liquid water, thereby increasing the output power density of the fuel cell and greatly improving the battery performance.
[0051] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0052] Example 1
[0053] (1) Preparation of the first cathode layer
[0054] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.9 g of TiO 2 (Specific surface area 200m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min, and the final ink is obtained. The ink is sprayed on one side of the PEM (Gore-12 microns) by ultrasonic spraying, and the Pt loading is 0.1mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the first cathode layer. The sample area is 50cm 2 , with a total thickness of 15 μm.
[0055] (2) Preparation of the second cathode layer
[0056] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd.-TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont-D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the first layer of the cathode using an ultrasonic spraying method, and the Pt loading was 0.1 mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the second cathode layer. The sample area is 50 cm 2 , with a total thickness of 18μm.
[0057] (3) Preparation of the third cathode layer
[0058] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.44 g of PTFE (specific surface area 150 m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min to obtain the final ink. The ink is sprayed on the second layer of the cathode by ultrasonic spraying, and the Pt loading is 0.1mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the third cathode layer. The sample area is 50cm 2 , with a total thickness of 21μm.
[0059] (4) Preparation of anode
[0060] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the other side of the PEM (Gore-12 microns) using an ultrasonic spraying method, with a Pt loading of 0.05 mg / cm 2 , and placed it in an oven for drying at 70°C for 5 minutes. The thickness of the anode catalyst layer is 2 μm.
[0061] Example 2
[0062] The difference from Example 1 is that TiO 2 (Specific surface area 200m 2 / g) powder added in an amount of 0.1 g.
[0063] Example 3
[0064] The difference from Example 1 is that TiO 2 (Specific surface area 200m 2 / g) powder added in an amount of 1.3g.
[0065] Example 4
[0066] The difference from Example 1 is that TiO 2 (Specific surface area 200m 2 / g) powder added in an amount of 1.7g.
[0067] Example 5
[0068] The difference from Example 1 is that TiO 2 The specific surface area is 100m 2 / g.
[0069] Example 6
[0070] The difference from Example 1 is that TiO 2 The specific surface area is 400m 2 / g.
[0071] Example 7
[0072] The difference from Example 1 is that TiO 2 The specific surface area is 500m 2 / g.
[0073] Example 8
[0074] The difference from Example 1 is that the same mass of hydrophilic silica particles (Huifu Nano HL-200; specific surface area 200m 2 / g) instead of TiO 2 .
[0075] Example 9
[0076] The difference from Example 1 is that PTFE (specific surface area 150m 2 / g) powder added in an amount of 0.05g.
[0077] Example 10
[0078] The difference from Example 1 is that PTFE (specific surface area 150m 2 / g) powder added in an amount of 0.88g.
[0079] Embodiment 11
[0080] The difference from Example 1 is that the specific surface area of PTFE is 100m 2 / g.
[0081] Example 12
[0082] The difference from Example 1 is that the specific surface area of PTFE is 400m 2 / g.
[0083] Example 13
[0084] The difference from Example 1 is that the specific surface area of PTFE is 50m 2 / g.
[0085] Embodiment 14
[0086] The difference from Example 1 is that the same mass of hydrophobic silica (Huifu Nano HB-151; specific surface area 150 m 2 / g) replace PTFE.
[0087] Embodiment 15
[0088] (1) Preparation of the first cathode layer
[0089] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.9 g of TiO 2 (Specific surface area 200m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min, and the final ink is obtained. The ink is sprayed on one side of the PEM (Gore-12 microns) by ultrasonic spraying, and the Pt loading is 0.05mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the first cathode layer. The sample area is 50cm 2 , with a total thickness of 13.5μm.
[0090] (2) Preparation of the second cathode layer
[0091] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the first layer of the cathode using an ultrasonic spraying method, and the Pt loading was 0.0.5 mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the second cathode layer. The sample area is 50 cm 2 , with a total thickness of 15 μm.
[0092] (3) Preparation of the third cathode layer
[0093] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.44 g of PTFE (specific surface area 150 m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min to obtain the final ink. The ink is sprayed on the second layer of the cathode by ultrasonic spraying, and the Pt loading is 0.05mg / cm 2Place it in an oven and dry it at 70°C for 5 minutes to prepare the third cathode layer. The sample area is 50cm 2 , with a total thickness of 16.5μm.
[0094] (4) Preparation of anode
[0095] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the other side of the PEM (Gore-12 microns) using an ultrasonic spraying method, with a Pt loading of 0.05 mg / cm 2 , and placed it in an oven for drying at 70°C for 5 minutes. The thickness of the anode catalyst layer is 2 μm.
[0096] Example 16
[0097] (1) Preparation of the first cathode layer
[0098] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.9 g of TiO 2 (Specific surface area 200m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min, and the final ink is obtained. The ink is sprayed on one side of the PEM (Gore-12 microns) by ultrasonic spraying, and the Pt loading is 0.15mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the first cathode layer. The sample area is 50cm 2 , with a total thickness of 16.5μm.
[0099] (2) Preparation of the second cathode layer
[0100] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the first layer of the cathode using an ultrasonic spraying method, and the Pt loading was 0.15 mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the second cathode layer. The sample area is 50 cm 2 , with a total thickness of 21μm.
[0101] (3) Preparation of the third cathode layer
[0102] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 0.44 g of PTFE (specific surface area 150 m 2 / g) powder, further add 15g of n-propanol and stir for 2min, further add 3.6g of ionomer solution (DuPont-D2020; 20% solid content), stir for 5min; further ball mill the mixed ink, the speed is set to 2000rpm, the time is 30min, further degassing treatment, the speed is set to 500rpm, the time is 5min to obtain the final ink. The ink is sprayed on the second layer of the cathode by ultrasonic spraying, and the Pt loading is 0.15mg / cm 2 Place it in an oven and dry it at 70℃ for 5min to prepare the third cathode layer. The sample area is 50cm 2 , with a total thickness of 25.5μm.
[0103] (4) Preparation of anode
[0104] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the other side of the PEM (Gore-12 microns) using an ultrasonic spraying method, with a Pt loading of 0.05 mg / cm 2 , and placed it in an oven for drying at 70°C for 5 minutes. The thickness of the anode catalyst layer is 2 μm.
[0105] Comparative Example 1
[0106] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of -ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on one side of the PEM (Gore-12 microns) using an ultrasonic spraying method, and the Pt loading was 0.05 mg / cm 2 , with a thickness of 2 μm, as the anode; placed in an oven and dried at 70 ° C for 5 min; sprayed on the other side of the PEM with a loading of 0.3 mg / cm 2 , with a thickness of 9 μm, as the cathode; place it in an oven and dry it at 70°C for 5 minutes; then place GDL (Toray-XGL-R-055) on both sides of the cathode and anode catalyst layers to obtain a membrane electrode (MEA) with a sample area of 50 cm 2 .
[0107] Comparative Example 2
[0108] (1) Preparation of the first cathode layer
[0109] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 5.5 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on one side of the PEM (Gore-12 microns) using an ultrasonic spraying method, and the Pt loading was 0.1 mg / cm 2 Place it in an oven and dry it at 70°C for 5 minutes to prepare the first cathode layer. The sample area is 50cm 2 , thickness is 14μm.
[0110] (2) Preparation of the second cathode layer
[0111] The only difference from step (1) is that the mass of the ionomer solution is 4.4 g.
[0112] (3) Preparation of the third cathode layer
[0113] The only difference from step (1) is that the mass of the ionomer solution is 2.8 g.
[0114] (4) Preparation of anode
[0115] In a container, 2.2 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E; 50.5% Pt & 49.5% C) particles were moistened with 19 g of water, and 15 g of n-propanol was further added for stirring for 2 min, and 3.6 g of ionomer solution (DuPont - D2020; 20% solid content) was further added and stirred for 5 min; the mixed ink was further ball milled at a speed of 2000 rpm for 30 min, and further degassed at a speed of 500 rpm for 5 min to obtain the final ink. The ink was sprayed on the other side of the PEM (Gore-12 microns) using an ultrasonic spraying method, with a Pt loading of 0.05 mg / cm 2 , and placed it in an oven for drying at 70°C for 5 minutes. The thickness of the anode catalyst layer is 2 μm.
[0116] Application Example 1
[0117] The electrochemical performance of the membrane electrode obtained in the above embodiments and comparative examples was tested. GDL used Toray-XGL-R-055, and the test conditions were: 70°C, 40% RH (relative humidity) for anode and cathode, anode / cathode stoichiometric ratio of 1.5 / 2, and anode and cathode back pressure of 150 kPa / 150 kPa.
[0118] For example, the polarization results of the membrane electrode of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, it can be seen that the performance of Example 1 is improved to varying degrees from low current density to high current density, and the performance improvement is particularly obvious at high current density.
[0119] The voltage value test results of the membrane electrodes prepared in the above embodiments and comparative examples at different current densities are detailed in Table 1 below.
[0120] Table 1
[0121]
[0122] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the above-mentioned fuel cell membrane electrode is constructed from the inside to the outside by adding hydrophilic nanoparticles in the first catalyst layer adjacent to the proton exchange membrane (PEM), and adding hydrophobic nanoparticles in the outermost layer of the cathode catalyst layer, that is, the third catalyst layer, to form a gradient design from hydrophilic to hydrophobic, which not only solves the proton conduction problem close to the PEM side, but also forms a capillary force gradient in the pores of the catalyst layer, which is beneficial to the transmission of oxygen and the discharge of liquid water, thereby improving the output power density of the fuel cell and greatly improving the battery performance. The above-mentioned preparation method is simple in process, suitable for process amplification, and can effectively solve the problem of water gas transmission in fuel cells.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fuel cell membrane electrode, comprising a cathode catalyst layer, a proton exchange membrane and an anode catalyst layer, characterized in that: The cathode catalyst layer comprises a first catalyst layer, a second catalyst layer and a third catalyst layer arranged in sequence, wherein the first catalyst layer is adjacent to the proton exchange membrane; The first catalytic layer, the second catalytic layer and the third catalytic layer independently include a catalyst and an ionomer, and the first catalytic layer contains hydrophilic nanoparticles, and the third catalytic layer contains hydrophobic nanoparticles.
2. The fuel cell membrane electrode according to claim 1, characterized in that: The hydrophilic nanoparticles include any one or more of nano-sized titanium dioxide particles, nano-sized hydrophilic fumed silica particles, nano-sized aluminum oxide particles, nano-sized polyvinyl alcohol particles, and nano-sized microcrystalline cellulose particles; Preferably, the specific surface area of the hydrophilic nanoparticles is 100-400 m 2 / g; Preferably, the mass ratio of the hydrophilic nanoparticles to the catalyst in the first catalytic layer is 0.05-0.8:
1.
3. The fuel cell membrane electrode according to claim 1, characterized in that: The hydrophobic nanoparticles include any one or more of nano-scale PTFE particles, nano-scale silicone resin particles, nano-scale hydrophobic fumed silica particles, and nano-scale fluoride hydrophobic agent particles; Preferably, the specific surface area of the hydrophobic nanoparticles is 100 to 400 m 2 / g; Preferably, the mass ratio of the hydrophobic nanoparticles to the catalyst in the third catalytic layer is 0.02-0.40:
1.
4. The fuel cell membrane electrode according to claim 1, characterized in that: The catalysts in the first catalytic layer, the second catalytic layer and the third catalytic layer are independently Pt / C or Pt-alloy / C catalysts. Preferably, the content of platinum in the catalysts of the first catalytic layer, the second catalytic layer and the third catalytic layer is 20-60wt%.
5. The fuel cell membrane electrode according to claim 1, characterized in that: The Pt loading of the first catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the second catalytic layer is 0.05-0.15 mg / cm 2 The Pt loading of the third catalytic layer is 0.05-0.15 mg / cm 2 .
6. The fuel cell membrane electrode according to claim 1, characterized in that: The ionomer is selected from any one or more of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, polymethylphenylsulfonic acid siloxane resin and sulfonated polystyrene-polyethylene copolymer resin; Preferably, in the first catalytic layer and / or the second catalytic layer and / or the third catalytic layer, the mass ratio of the ionomer to the carbon in the catalyst is 0.2 to 2.0:
1.
7. A method for preparing a fuel cell membrane electrode according to any one of claims 1 to 6, characterized in that: include: Step S1, placing a first catalytic layer dispersion on one surface of a proton exchange membrane to form a first catalytic layer, wherein the first catalytic layer dispersion comprises a catalyst, an ionomer, hydrophilic nanoparticles and a solvent; Step S2, placing a second catalytic layer dispersion on the surface of the first catalytic layer to form a second catalytic layer, wherein the second catalytic layer dispersion comprises a catalyst, an ionomer and a solvent; Step S3, placing a third catalytic layer dispersion on the surface of the second catalytic layer to form a third catalytic layer, wherein the third catalytic layer dispersion comprises a catalyst, an ionomer, hydrophobic nanoparticles and a solvent.
8. The preparation method according to claim 7, characterized in that: The content of the catalyst in the first catalyst layer dispersion is 1-20wt%; and / or, the content of the catalyst in the second catalyst layer dispersion is 1-20wt%; And / or, the content of the catalyst in the third catalytic layer dispersion is 1-20 wt %.
9. The preparation method according to claim 7, characterized in that: The solvents in the first catalytic layer dispersion liquid, the second catalytic layer dispersion liquid and the third catalytic layer dispersion liquid are independently any one or more of water, methanol, ethanol, ethylene glycol, propanol, isopropanol and glycerol.
10. A fuel cell, characterized in that: The invention comprises a fuel cell membrane electrode as described in any one of claims 1 to 6, or a fuel cell membrane electrode prepared by the preparation method as described in any one of claims 7 to 9.
Citation Information
Cited By
Method for improving surface oxidation stability of proton exchange membrane of fuel cell
CN120127183A